Counter examples to adjudicating a towers of hanoi contest - Er, M.C. (International journal of computer mathematics, 1987)
This paper points out the inconsistency in the criteria for adjudicating a Towers of Hanoi contest proposed by Wood. Counter examples to some of Wood's claims are given. In particular, the shortest path for transforming a configuration of n discs to another configuration may not be unique. Finally, a set of better criteria for adjudicating a Towers of Hanoi contest is proposed.